Analisis Pengaruh PDB dan Rasio Keuangan terhadap Harga Saham Perusahaan Big-Cap Sektor Properti yang Terdaftar di BEI pada Masa Pandemi Tahun 2020 - Monica Seftaviani Sijabat; Lia Yuliana (Seminar Nasional Official Statistics, 2021)
The COVID-19 pandemic that occurred in Indonesia had a major impact on the capital market. The stock prices of all sectors experienced significant fluctuations. The property sector is the sector with the lowest share price in 2020. This can be seen from the movement of the property sector index which experienced a downward trend. The movement of the sector index is influenced by the movement of stock prices of large-cap companies (Big-Cap), where the average share price of Big-Cap companies tends to decrease compared to the fourth quarter of 2019. This study aims to determine what variables affect prices. Big-Cap company shares in the property sector in 2020. Panel data regression analysis was used to determine the effect of GDP, CR, DER, ROE, and PBV on the share price of Big-Cap companies in the property sector. The results showed that DER and ROE had a negative effect, while PBV had a positive effect on the stock price of Big-Cap companies in the property sector significantly. Variables CR and GDP have no significant effect on the share price of Big-Cap companies in the property sector. Therefore, investors who invest in shares of Big-Cap companies in the property sector need to consider the value of financial ratios, especially DER, ROE, and PBV before making investment decisions.